Stroke Complicating Acute ST Elevation Myocardial Infarction—Current Concepts - Bhandari, Monika; Vishwakarma, Pravesh; Sethi, Rishi; Pradhan, Akshyaya (International Journal of Angiology, 2019)
Myocardial infarction (MI) is one of the leading causes of mortality today both in developed and developing countries alike. Advancement in the pharmacotherapy and revascularization techniques has resulted in drastic improvement in survival. Most of the complications of MI can be managed adequately resulting in reduced mortality from MI in the recent years. However, mortality from stroke following acute MI remains high even today. Here, we discuss the incidence, risk factors, and management of stroke following acute ST elevation MI.
Keywords: ischemic stroke; thrombolysis; CT scan; reperfusion therapy